FOXM1b, which is present at elevated levels in cancer cells, has a greater transforming potential than FOXM1c - Lam, Andy K.; Ngan, Adaline W.; Leung, Man-Hong; Kwok, Davis C.; Liu, Vincent W.; Chan, David W.; Leung, Wai Ying; Yao, Kwok-Ming (Frontiers in Oncology, 2013)
The Forkhead box (FOX) M1 transcription factor is required to maintain the proliferation of cancer cells. Two transcriptionally active isoforms of FOXM1, FOXM1b and FOXM1c, have been identified, but their functional differences remain unclear. FOXM1c is distinguished from FOXM1b by an extra exon (exon Va) that contains an ERK1/2 target sequence. Based on a literature search and quantitative PCR analysis, we concluded that FOXM1b is the predominant isoform that is overexpressed in cancers. The further characterization of FOXM1b and FOXM1c revealed two interesting differences. First, FOXM1b exhibited a higher transforming ability than FOXM1c in a soft agar assay. Second, the transactivating activity of FOXM1c, but not that of FOXM1b, was sensitive to activation by RAF/MEK/MAPK signaling. Importantly, the MEK1 activation of FOXM1c was associated with proteolytic processing to generate short forms that might represent constitutively active forms missing the N-terminal inhibitory domain; in contrast, the proteolytic processing of FOXM1b did not require MEK1 activation. Our findings suggest that FOXM1b is functionally more active. These results provide novel insights into the regulation of FOXM1 activity and its role in tumorigenesis.